(untitled) (Philosophy and Progress, 2016)
In this twenty first century, market became more competitive and existing players have to fight in the ocean and have to survive after sacrificing own blood. However, every market players wants to live in the blue ocean. Thus, they attempt to develop and market the right product for right consumers. However, this is most important to understand how consumers define their need and how they want to meet their needs. It is important to understand the difference which one is need for which customer and which one want or demand to whom. In this stage, it raises the question to have better a deep insight about consumers psychology. If a marketer can understand his/her consumers psychology, he/she might easily pick up the best weapon to hit the consumers and to get them into the spider net spread to catch them all. Today, consumers are very much informative and they know well what they want and what is going on. So, marketers need to be very careful in designing marketing strategy to offer the best brand with a sense to deliver the message or communicating the consumer about the brand without bothering or irritating the consumer. Creating the best brand depends on how well a marketer can read consumers mind regarding the requirement and final success depends on how well they could communicate them through different marketing techniques/tools. These all require a good sense of consumer psychology for the marketers to draw a perfect image of the consumers in their marketing strategy development. The marketing techniques used by all marketers to attract consumers, produce new product, attract through different activities like coupon, demonstration, event show, trade show, advertising, celebrity endorsement are almost same. However, success run behind the winner who can better adopt consumers psychology. Philosophy and Progress, Vol#55-56; No#1-2; Jan-Dec 2014